A Review on Various Traffic Event Detection Techniques - Kashyap, Sonam; Gupta, Mohit (International Journal of Computer Sciences and Engineering, 2018)
Unusual event detection is the task of identifying the unusual events in a given region or area. Over last few years, Unusual event detection has received much of attraction due to its wide range of applications like fall detection, accident detection, lane change detection, red light running, traffic video surveillance . It is a very consequential and efficacious research topic in field of computer vision and video processing. Consequently, identification of unusual event from a given sequence of video frames becomes pertinent. However, task of detecting unusual event in motion becomes tricky due to various challenges like dynamic scene changes, illumination variations, and presence of shadow, camouflage and bootstrapping problem. To lessen the consequences of these problems, researchers have proposed number of new approaches. This paper provides a brief classification of the classical approaches for unusual event detection. Further, paper reviews recent research trends to detect unusual events along with discussion of key points and limitations of each approach.